Pengembangan Aplikasi Manajemen Finance Accounting pada Perusahaan Jasa Konstruksi berbasis Mobile (Studi Kasus : AMF-HAQ) - Ibnu Adzakir; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
AMF-HAQ company was established in West Jakarta in 2006 which is engaged in construction services. In carrying out its business processes, the accounting division encountered several problems that could hinder AMF-HAQ from developing. The accounting division still uses Microsoft Excel to record financial reports which can cause piles of files and the absence of integrated data backups. This can result in financial data being vulnerable to data loss, long data retrieval processes, and a lack of visual analysis of data in financial reports. To assist the development of the company towards business expansion, an information management application for recording financial data is needed. This application has features to support the company's accounting cycle including recording income and expenditure reports, financial journals, ledgers, and balance sheets. This application is built using the React Native framework in mobile-based development so that it can run on Android and iOS platforms, also uses GraphQL for query processing into the MongoDB database for data storage. For unit testing on the application using the white-box method and validation testing using black-box. Testing non-functional requirements using compatibility on android 5.0 and android 9 devices. The test results get a value of 100% in meeting the needs and are valid.